2002
DOI: 10.1159/000063102
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Continuous Hemodiafiltration for Patients with Congestive Heart Failure

Abstract: Background/Aims: The basic principle of treatment of congestive heart failure is achieving adequate control of preload and afterload through enhancement of cardiac contractility. In severe cases, however, we have usually applied continuous hemodiafiltration (CHDF) as a type of mechanical support. In this study, we investigated hemodynamic changes caused by CHDF in patients with congestive heart failure. Methods: We treated seven patients with congestive heart failure complicated by multiple organ failure by CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Indeed, in a recent review, Mehta and colleagues [ 18 ] concluded that there are no established guidelines for the modulation of fluid balance by means of diuretics or RRT in patients with organ dysfunction. Although diuretics can influence fluid balance, there is no evidence that their use can alter outcome in ARF [ 19 ], and the evidence for a beneficial effect of RRT on outcome in patients with multiple organ failure is also debated [ 20 - 22 ]. The findings of the present study should stimulate further studies to investigate the role of fluid balance on prognosis in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a recent review, Mehta and colleagues [ 18 ] concluded that there are no established guidelines for the modulation of fluid balance by means of diuretics or RRT in patients with organ dysfunction. Although diuretics can influence fluid balance, there is no evidence that their use can alter outcome in ARF [ 19 ], and the evidence for a beneficial effect of RRT on outcome in patients with multiple organ failure is also debated [ 20 - 22 ]. The findings of the present study should stimulate further studies to investigate the role of fluid balance on prognosis in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous hemodiafiltration had favorable effects on blood pressure and urine output not only because it had a less adverse effect on hemodynamics, but also because continuous elimination of cytokines and other humoral mediators responsible for unstable hemodynamics was possible in this group. We have frequently reported that CHDF is effective in eliminating humoral mediators and other toxic substances (18–22). Bellomo et al (23) and Bohrer et al (24) have also reported that CHDF is effective in eliminating humoral mediators.…”
Section: Discussionmentioning
confidence: 99%
“…6,[10][11][12] CHDF therapy has also been reported to be effective in the treatment of CHF. 8) Furthermore, CHDF is being anticipated as a superior method for cytokine excision 8) compared with ultrafiltration. Cytokine excision may be effective in heart failure treatment.…”
Section: Discussionmentioning
confidence: 99%
“…6,7) It has been reported that continuous hemodiafiltration (CHDF) is also a possible alternative volume reduction therapy for diuretics and is being anticipated as a method for cytokine excision. 8) However, there is not enough data available on its efficacy and safety. We therefore conducted this study to evaluate the efficacy and safety of CHDF therapy for acute decompensated heart failure (ADHF).…”
mentioning
confidence: 99%